KUALITAS PAPAN PARTIKEL KAYU KARET (Hevea brasiliensis Muell. Arg) DAN BAMBU TALI (Gigantochloa apus Kurz) DENGAN PEREKAT LIKUIDA KAYU - Ary Widiyanto (Jurnal Penelitian Hasil Hutan, 2011)
As an effort to utilize rubber wood waste and the abundant resource of tali bamboo a study of producing particle board using a mix of the two materials was conducted. In addition, in order to find an alternative to synthetic adbesive, natural adhesive of wood liquid was used. This research was conducted in a 3 x 3 factorial analisys in acomplete randomized block design with two replicates. The factors studied were the type of particles (rubber, bambino rope and mixtures with a ratio of 50:50 by oven dry weight) and levels of adhesive (10%, 15% and 20%. Results show that wood liquids adhesive is characterised with pH <1, riscosity 2,03 poise, solid content 91%, gelatin time (90) 9 min 48 sec, specific gravity 1,153 and having black colour. The characteristics do not fulfil requirement of SNI 06-0121-1987 for phenol adhesive. The producced particle board has a density of 0,83 g/cm², moisture content 6,9%, thickness swelling 19%, water adsorbtion 28%, MOE 10540 kgf/cmỉ, MOR 258 kgf/cm², and Internal Bond (IB) 2,2 kgf/cm². The characteristics also do not fulfill the requirement ofSNI 03-2105-1996for medium density particleboard. Further research is still needed to meet the SNI requirements.